2021
DOI: 10.3906/zoo-2102-20
|View full text |Cite
|
Sign up to set email alerts
|

First report on mild insecticide resistance in newly established Aegean Aedesalbopictus populations of Turkey

Abstract: a total of 2.474 ZIKV cases were reported from European Union/European Economic Area (EU/EEA) countries (ECDC, 2019a).Ae. albopictus is native to southeast Asia (Gratz, 2004). However, its invasive nature has allowed it to spread from East Asia and Indian Ocean islands (subtropical / tropical areas) to all continents except Antarctica (Caminade et al., 2012;Benedict et al., 2007). The invasion potential of this species and its easy spread to the world is due to its ecological plasticity (Scholte & Schaffner, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Albopictus in Türkiye there have been data set of insecticide resistance of Ae. Albopictus Türkiye populations except for the one study reported from the Aegean populations [15] . The development of insecticide resistance in vector mosquito populations may result in a decline in effective control strategies [20] .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Albopictus in Türkiye there have been data set of insecticide resistance of Ae. Albopictus Türkiye populations except for the one study reported from the Aegean populations [15] . The development of insecticide resistance in vector mosquito populations may result in a decline in effective control strategies [20] .…”
Section: Introductionmentioning
confidence: 94%
“…Then, sedentary populations have been reported from the North Eastern Black Sea region [14] . Finally, the Aegean region populations have been reported from Aydın and Muğla [15] . Currently, mosquito control management is a major strategy for the prevention and control of mosquito-borne diseases because of the lackesness of influential drugs and vaccines against most mosquito-borne diseases [16,17] .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in 2018, it appeared in the Aegean region in Izmir (Aliaga port). Recent research by different authors and our group has revealed that the species has spread along seaside cities in the Black Sea, Marmara, and Aegean regions, as well as some inland cities in central and east Anatolia (Oter et al 2013, Demirci et al 2021a, Yavasoglu 2021.In Europe, two distinct climatic lineages of A. albopictus exist: the Italian lineage, which descended from the American-derived temperate climate Japanese lineage, and the Albanian lineage, which descended from the Chinese lineage (Kamgang et al 2011, Žitko et al 2011, Ruiling et al 2018. Previous genetic studies suggest that the origin of the Greek lineage was an admixture between Central Italy and Albania lineages, and the origin of A. albopictus populations from the eastern Black Sea region originated in the north Italian lineage (Sherpa et al 2018).…”
Section: Introductionmentioning
confidence: 99%